NEUROCOGNITIVE HETEROGENEITY IN BORDERLINE PERSONALITY DISORDER: THE ROLE OF CHILDHOOD SEXUAL ABUSE. - Cabrera, Horus Laffite; Rodríguez-Otero, Fernando; Alonso-Sosa, Raquel; Martínez-Huidobro, María F.; Hernández-Fleta, José L.; Díaz-Garrido, Juan Antonio (Panamerican Journal of Neuropsychology / Cuadernos de Neuropsicología)
Childhood sexual abuse (CSA) is strongly associated with borderline personality disorder (BPD). This cross-sectional study investigated clinical and neurocognitive differences in 193 women aged 20 to 39 years diagnosed with BPD, comparing those with a history of CSA (n = 78) and those without (n = 115). Participants completed standardized psychometric and neuropsychological assessments focused on impulsivity, core BPD symptoms, and cognitive functioning. Women with CSA showed greater clinical severity, including higher rates of self-harm, suicide attempts, dissociative and psychotic symptoms, along with elevated impulsivity and attention-deficit/hyperactivity disorder (ADHD)–related traits. Neuropsychological testing revealed significant deficits in attention, processing speed, and cognitive flexibility, along with lower performance on Stroop tasks assessing divided attention and interference control. While working memory and verbal fluency differences remained within normative ranges, age-stratified analysis revealed marked long-term memory impairments in the CSA group aged 30–39. These results suggest that neurocognitive deficits in BPD are not universal but may reflect the cumulative impact of early trauma and age. Trauma-informed assessment and tailored cognitive interventions may support more accurate profiling and inform tailored therapeutic strategies in this highrisk subgroup.